Effect of starvation on the distribution of positional isomers and enantiomers of triacylglycerol in the diatom Phaeodactylum tricornutum - Rezanka, Tomáš; Lukavský, Jaromír; Nedbalová, Linda; Kolouchová, Irena; Sigler, Karel (Phytochemistry, 2012)
The diatom Phaeodactylum tricornutum was cultivated in a standard medium and under sulfur, silicon, nitrogen and phosphorus starvation and its triacylglycerols (TAGs) were analyzed by RP-HPLC/MS-APCI. Nearly 100 molecular species of polyunsaturated TAGs were identified. RP-HPLC was used to isolate positional isomers of TAGs, which were further separated by chiral HPLC. First eluted were those TAGs that have an eicosapentaenoic acid moiety in the sn-1 position. The ratios of symmetrical to asymmetrical TAGs in P. tricornutum were affected under sulfur-, nitrogen-, phosphorus- and silica-starvation, i.e. in cultivations involving cells in nutrient stress. The ratios of positional TAGs and also the proportions of enantiomers were changed. The ratios of symmetrical to asymmetrical TAGs in the control and under N- and P-starvation were very close. In the control, the ratio of 1,2-dipalmitoyl-3-eicosapentaenoyl-rac-glycerol to 1,3-dipalmitoyl-2-eicosapentaenoyl-rac-glycerol was 3:1 and the ratio of 1,2-dieicosapentaenoyl-3-palmitoyl-rac-glycerol to 1,3-dieicosapentaenoyl-2-palmitoyl-rac-glycerol was 9:1. Under N-starvation the ratios were reversed irrespective of the presence or absence of silicate in the medium. A similar pattern was found in P- and S-starvation.
Keywords: rozsivky; Culture Media; Eicosapentaenoic Acid; stereoizomerie; Triglycerides; Diatoms; kyselina eikosapentaenová; Stereoisomerism; triglyceridy; kultivační média